SINTESIS SCAFFOLD ALGINAT-KITOSAN-KARBONAT APATIT SEBAGAI BONE GRAFT MENGGUNAKAN METODE FREEZE DRYING - M R Aufan (Jurnal Biofisika, 2012)
Scaffold is a three dimensional structure that can be used as temporary supporting media in body tissue repairmen process. Some properties that must be owned by the scaffold  are  porous,  biocompatible,  biodegradable,  bioactive,  and  have  sufficient mechanical  strength  to  sustain  the  new  tissue  growth.  In  this  present  study,  the scaffold will be synthesized for bone tissue repairmen using alginate, chitosan, and carbonate apatite. The variation  ratio of  alginate  and  chitosan  used in  this study  was 100% alginate,  2:1.  1:1,  1:2,  and  100% chitosan  with  the same  mass of  carbonate apatite  for  each  variation,  which  is  0.1  gram.  The  results  of  mixing  the  three ingredients were then  freeze-dried  in  order to obtain the  porous  characteristic of  the scaffold. From the results of the FTIR, the crosslinking process between the carboxyl groups  on  alginate  characterized  by  the  emergence  of  the  peak  at  1620  cm-1 frequency and the ionic bonding between alginate and chitosan are observed. The results  of  SEM  examination  stated:  first,  the  properties  of  porous  scaffold  is successfully  acquired  using  freeze  drying  method;  second,  the  variations  in  the composition  of  alginate  and  chitosan  as  well  as  the  addition  of  carbonate  apatite scaffold affect the structure formed. Composition of alginate: chitosan = 1:1 tends to produce  a  more  dense  scaffold  compared  with  other  compositions;  third,  the existence of carbonate apatite is observed on the surface of the scaffold.